Artificial Intelligence (AI) dan Penerapan dalam Dunia Bisnis - Joko Musridho, Raja; Mudi Priyatno, Arif (Journal of Social and Community Service, 2023)
Artificial Intelligence (AI) is something that allows machine to be able to do what humans can do. Intelligent needs knowledge, experience and capability in decision-making and act. Based on the data acquired from academicians whose expertise are not in AI, there is assumption that AI is things that related to robots and always have physical shape. Therefore, re-explanation of basics of AI needs to be done in order to direct the AI development plan in Universitas Pahlawan to focus not only to the robots that have physical shape. Furthermore, applications of AI in the business world was explained to strengthen the basics of AI that have been delivered. The result of the webinar got one question about the impact of AI to the jobs availability.